Fisioterapia obstétrica y reeducación del suelo pélvico durante el embarazo en pacientes atentidas en el Instituto de ginecología y osteoporosis en el periodo diciembre 2011 a mayo 2012 - Benavidez Sánchez, Paola Silvana (2012)
We present to consideration of you gentlemen readers, the topic that through the present work, he/she has relationship with the different Techniques of Obstetric Rehabilitation applying to woman in state of gestation pains in the Institute of Gynecologic and Osteoporosis of Riobamba, after having carried out an investigation of bibliographical sources, you has ended up concluding that it is a study of new investigation for our means. The pprescription of the combination, thay seek to follow the general lines of the medical therapy, always in people’s that suffer pathologies that have relationship with that temporary or permanent affection of their anatomy skeletal muscle benefit. Hence, in Institute of Gynecologic and Osteoporosis of Riobamba, during the period december 2001 and may 2012, the application of different treatment techniques was allowed accordind to each pathological case.